Comparison of Revalor®-S and Synovex® Plus™ implants for heavyweight, short-fed, yearling steers - Gerry L. Kuhl; A.S. Flake; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1999)
One hundred four Hereford x Angus steers averaging 897 lb were implanted with Revalor®- S or Synovex® Plus™ and fed a high concentrate diet for 82 days. Feed efficiencies and daily gains were not different between the two implant groups. Although most carcass characteristics were similar, Revalor-S tended (P<.09) to yield a higher percentage of carcasses that graded USDA Choice or better.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Steers; Finishing; Revalor-S; Synovex plus